Developing and applying a 'living guidelines' approach to WHO recommendations on maternal and perinatal health. Issue 4 (17th August 2019) - Vogel, Joshua P; Dowswell, Therese; Lewin, Simon; Bonet, Mercedes; Hampson, Lynn; Kellie, Frances; Portela, Anayda; Bucagu, Maurice; Norris, Susan L; Neilson, James; Gülmezoglu, Ahmet Metin; Oladapo, Olufemi T
Abstract : How should the WHO most efficiently keep its global recommendations up to date? In this article we describe how WHO developed and applied a 'living guidelines' approach to its maternal and perinatal health (MPH) recommendations, based on a systematic and continuous process of prioritisation and updating. Using this approach, 25 new or updated WHO MPH recommendations have been published in 2017–2018. The new approach helps WHO ensure its guidance is responsive to emerging evidence and remains up to date for end users.